Identification of aluminium-responsive genes in rice cultivars with different aluminium sensitivities - Zhang, J.; He, Z.; Tian, H.; Zhu, G.; Peng, X.
Aluminium (Al)toxicity is a worldwide problem in agricultural practice. Based on evidence that Al resistance may be an inducible process and that rice is one of the most Al-resistant crops, the gene transcriptional responses to Al were investigated in two contrasting rice cultivars (resistant XN1 versus sensitive XX2)using differential display reverse transcription- PCR (DDRT-PCR)in combination with northern blotting analysis. A total of 37 genes were identified as differentially expressed, of which five have been previously known as Al regulated while the others are novel genes. Among the up-regulated genes, four encode ion transporters, two are involved in signal transduction, and five in the synthesis of cysteine and metallothionein. These could be members that are potentially involved in Al adaptation or resistance. On the other hand, the transcription of 17 genes was strongly inhibited under Al stress. These genes are associated with cytoskeletal dynamics and metabolism, and could be possible targets associated with Al toxicity. All of these differentially expressed genes may represent candidates that function in Al responses. The results suggest, at the transcriptional level, that cytoskeletal disruption may be associated with Al toxicity, whereas ion transport and sulphur metabolism could play major roles in Al adaptation or tolerance in rice.
Keywords: AL STRESS; GENE EXPRESSION; RESISTANCE; RICE; TOXICITY